Μελέτη της οξείδωσης των λιπαρών οξέων σε βοδινό κρέας παρουσία κυπριακών οίνων υπό συνθήκες συσκευασίας κενού - Γιάγκου, Χριστιάνα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The present study investigates the nature of the oxidation of fatty acids in minced beef meat in different samples from longissimus dorsi muscle in the presence or the absence of white or red wine. Cypriot wines were used, Xinisteri as the white wine and Maratheftiko as the red wine. After the preparation of the samples was completed they were placed in pairs in special little bags and then they placed in vacuum packaging to exclude oxygen from the package. The samples were placed in refrigerator at 4 ⁰C and at certain time intervals were withrowed and store at at -70⁰C. The Thiobarbituric acid method protocol (TBARS) was followed for the determination of the lipid oxidation accompanied by measurements of absorption for the malonyl dialdehyde (MDA) aducts on the Vis-Spectrometer. Quantification for each lipid acid was done by gas chromatography. Fatty acids Methyl Esters (FAME) were prepared by esterification of the acids previously extracted from meat samples using the Folch method. According to the results, in mince beef samples no high increase of the MDA concentration was observed as it would expected if the meat samples were in contact with the atmospheric oxygen. The meat samples, which had previously marinated in white or red wine, show higher concentration of MDA than the control. The results for the quantification at the time (days) 0, 4, 6, 11 in control samples, the oxidation of oleic acid was increased than the oxidation of the other fatty acids. Arachidonic acid and linoleic acid has fluctuations of % content which had found in low concentrations over time. Similar pattern for the lipid oxidation was also recorded in FAME analysis, where the quantification of the fatty acids shoed higher oxidative destruction for the oleic acid in the wine samples than the control samples. Arachidonic and linoleic acids also showed small differences in their percentage during the experiment for all the samples. These results show that although the fatty acid oxidation for the meat samples is smaller when the samples are stored under vacuum, the lipid oxidation is activated by the metal ions, like Fe2+, which form peroxides and free radicals when in contact with aqueous-ethanolic wine solutions.
Keywords: Beef meat; Lipids oxidation; Fatty acids Methyl Esters (FAME); Thiobarbituric acid method protocol (TBARS); Cyprus Wines; Xinisteri; Maratheftiko; Vacuum packing; GC/MS; Βοδινό κρέας; Βοδινό λίπος; Οξείδωση λιπαρών οξέων; Κυπριακοί οίνοι; Ξυνιστέρι; Μαραθεύτικο; Συσκευασία κενού